Association of burnout with depression in pharmacists: A network analysis - He, Mu; Li, Kuiliang; Tan, Xuejiao; Zhang, Lei; Su, Chang; Luo, Keyong; Luo, Xi; Liu, Chang; Zhao, Mengxue; Zhan, Xiaoqing; Wang, Qian; Cen, Jing; et al. (Frontiers in Psychiatry, 2023)
Background: Burnout and depression have overlapping symptoms, but the extent of overlap remains unclear, and the complex relationship between burnout and depression in pharmacists is rarely explored. Methods: We investigated burnout and depression in 1322 frontline pharmacists, and explored the complex relationship between burnout and depression in those pharmacists using network analysis. Results: Network analysis showed that there were 5 communities. A partial overlap was found between burnout and depressive symptoms in pharmacists. The nodes MBI-6 (I have become more callous toward work since I took this job), D18 (My life is meaningless) and D10 (I get tired for no reason) had the highest expected influence value. D1 (I feel down-hearted and blue) and D14 (I have no hope for the future) were bridge symptoms connected with emotional exhaustion and reduced professional efficacy, respectively. Conclusions: A partial overlap exists between burnout and depressive symptoms in pharmacists, mainly in the connection between the emotional exhaustion and reduced professional efficacy and the depressive symptoms. Potential core targets identified in this study may inform future prevention and intervention.